Free-space QKD system hacking by wavelength control using an external laser - Lee, Min Soo; Woo, Min Ki; Jung, Jisung; Kim, Yong-Su; Han, Sang-Wook; Moon, Sung (OPTICAL SOC AMER, 2017)
We develop a way to hack free-space quantum key distribution (QKD) systems by changing the wavelength of the quantum signal laser using an external laser. Most free-space QKD systems use four distinct lasers for each polarization, thereby making the characteristics of each laser indistinguishable. We also discover a side-channel that can distinguish the lasers by using an external laser. Our hacking scheme identifies the lasers by automatically applying the external laser to each signal laser at different intensities and detecting the wavelength variation according to the amount of incident external laser power. We conduct a proof-of-principle experiment to verify the proposed hacking structure and confirm that the wavelength varies by several gigahertzes to several nanometers, depending on the intensity of the external laser. The risk of hacking is successfully proven through the experimental results. Methods for prevention are also suggested. (C) 2017 Optical Society of America
Keywords: QUANTUM KEY DISTRIBUTION; INDUCED DAMAGE; CRYPTOGRAPHY; PLUG; BAND; COMMUNICATION; DAYLIGHT